Ukuran Dewan: Penentu Atau Pelengkap? Analisis Pengaruh ESG Dan Dividen Terhadap Nilai Perusahaan - Renny Wulandari (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
The aims of this study are to examine the influence of ESG performance on firm value and to evaluate whether board size can moderate the relationship between ESG and firm value. Research data was collected from companies listed on the LQ45 on IDX during the period 2015–2021. The results show that overall ESG performance has a negative and significant impact on firm value, while dividends have a positive effect on firm value. This study shows that investment in ESG performance has not promised a return in increasing the value of the company financially, and board size has a pure moderating effect. This evidence showed that the size of the board becomes inefficient if it is too large. The number determines the success of coordination and the delivery of information. Finally, companies can improve ESG performance, which in turn can increase capital flows and company growth, as well as provide an understanding to both internal and external investors about the importance of ESG for sustainable investment in the long term.